2004
DOI: 10.1111/j.1365-2648.2004.03171.x
|View full text |Cite
|
Sign up to set email alerts
|

The development of evidence‐based nursing interventions: methodological considerations

Abstract: Use of the model could facilitate effective communication among nurses, researchers and educators when discussing the development and testing of nursing interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
161
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(167 citation statements)
references
References 16 publications
0
161
0
6
Order By: Relevance
“…[4] 3. LITERATURE REVIEW According to van Meijel et al [9] an essential element in designing an intervention is the comprehension of the problem to be addressed by the intervention, the nature of service needs of clients and whether other interventions are available. The literature has revealed that cognitive behavioral therapy (CBT) is effective and is one of the most common therapy provided to university students for prevention or early intervention of depression and anxiety.…”
Section: The Problemmentioning
confidence: 99%
See 4 more Smart Citations
“…[4] 3. LITERATURE REVIEW According to van Meijel et al [9] an essential element in designing an intervention is the comprehension of the problem to be addressed by the intervention, the nature of service needs of clients and whether other interventions are available. The literature has revealed that cognitive behavioral therapy (CBT) is effective and is one of the most common therapy provided to university students for prevention or early intervention of depression and anxiety.…”
Section: The Problemmentioning
confidence: 99%
“…[9] The intervention described in this paper is regarded as an evidence-based nursing intervention targeting female university students who demonstrate symptoms of psychological distress with symptoms of depression and/or anxiety.…”
Section: Design Of the Preliminary Interven-tionmentioning
confidence: 99%
See 3 more Smart Citations